Phospholipase C-Related but Catalytically Inactive Protein Modulates Pain Behavior in a Neuropathic Pain Model in Mice. (2nd May 2013) - Kitayama, Tomoya; Morita, Katsuya; Sultana, Rizia; Kikushige, Nami; Mgita, Keisuke; Ueno, Shinya; Hirata, Masato; Kanematsu, Takashi
Background: An inositol 1, 4, 5-trisphosphate binding protein, comprising 2 isoforms termed PRIP-1 and PRIP-2, was identified as a novel modulator for GABAA receptor trafficking. It has been reported that naive PRIP-1 knockout mice have hyperalgesic responses. Findings: To determine the involvement of PRIP in pain sensation, a hind paw withdrawal test was performed before and after partial sciatic nerve ligation (PSNL) in PRIP-1 and PRIP-2 double knockout (DKO) mice. We found that naive DKO mice exhibited normal pain sensitivity. However, DKO mice that underwent PSNL surgery showed increased ipsilateral paw withdrawal threshold. To further investigate the inverse phenotype in PRIP-1 KO and DKO mice, we produced mice with specific siRNA-mediated knockdown of PRIP s in the spinal cord. Consistent with the phenotypes of KO mice, PRIP-1 knockdown mice showed allodynia, while PRIP double knockdown (DKD) mice with PSNL showed decreased pain-related behavior. This indicates that reduced expression of both PRIPs in the spinal cord induces resistance towards a painful sensation. GABAA receptor subunit expression pattern was similar between PRIP-1 KO and DKO spinal cord, while expression of K + -Cl-cotransporter-2 (KCC2), which controls the balance of neuronal excitation and inhibition, was significantly upregulated in DKO mice. Furthermore, in the DKD PSNL model, an inhibitor-induced KCC2 inhibition exhibited an altered phenotype from painless to painful sensations. Conclusions: Suppressed expression of PRIPs induces an elevated expression of KCC2 in the spinal cord, resulting in inhibition of nociception and amelioration of neuropathic pain in DKO mice.